2018
DOI: 10.1097/igc.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Ovarian Endometriosis on the Prognosis of Ovarian Clear Cell Carcinoma

Abstract: Ovarian clear cell carcinoma with endometriosis was found more frequently in younger women and had a higher incidence of early-stage disease and a lower incidence of lymph node metastasis compared with OCCC without endometriosis. Ovarian endometriosis was associated with improved prognostic factors and a better DFS and OS even in stage I disease. Ovarian endometriosis was an independent prognostic factor for OCCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 15 publications
3
20
2
2
Order By: Relevance
“…OCCC with endometriosis has been reported to be associated with early stage and good prognosis [16,17]. Meanwhile no difference in prognosis of OCCC according to the presence of endometriosis has been reported [18,19]. In the present study, about one-third of patients had endometriosis.…”
Section: Discussioncontrasting
confidence: 43%
“…OCCC with endometriosis has been reported to be associated with early stage and good prognosis [16,17]. Meanwhile no difference in prognosis of OCCC according to the presence of endometriosis has been reported [18,19]. In the present study, about one-third of patients had endometriosis.…”
Section: Discussioncontrasting
confidence: 43%
“…OCCC with endometriosis has been reported to be associated with early stage and good prognosis [16,17]. Meanwhile no difference in prognosis of OCCC according the presence of endometriosis has been reported [18,19]. In the present study, about one third of patients had endometriosis.…”
Section: Discussioncontrasting
confidence: 42%
“…A meta-analysis of evidence from 10 cohort studies also concluded that endometriosis is not a prognostic factor for the survival of OCCC patients [ 34 ]. A study conducted in Korea found that only in FIGO stage I patients was endometriosis an independent prognostic factor [ 19 ]. However, studies conducted in China found no prognostic role of endometriosis in OCCC patients [ 2 ], even when the tumor was confined to FIGO stage I [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size in these studies was limited and the last study spanned over a period of 27 years, during which time considerable changes in adjuvant therapies took place. The other studies also did not reach a consensus about the prognostic role of endometriosis [ 2 , 18 , 19 ]. The purpose of the present study was to investigate whether concomitant endometriosis affects the survival of patients with pure OCCC and to identify other prognostic factors in these patients.…”
Section: Introductionmentioning
confidence: 99%